2020
DOI: 10.1002/adma.202004080
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Exciton Transport with a Long Diffusion Length in Layered Perovskites with Organic Cation Functionalization

Abstract: Layered perovskites have been employed for various optoelectronic devices including solar cells and light‐emitting diodes for improved stability, which need exciton transport along both the in‐plane and the out‐of‐plane directions. However, it is not clear yet what determines the exciton transport along the in‐plane direction, which is important to understand its impact toward electronic devices. Here, by employing both steady‐state and transient photoluminescence mapping, it is found that in‐plane exciton dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Pioneering studies on 2D perovskite films provide insights into the mechanisms of crystallization and orientation, suggesting that an interlayer interaction among adjacent bulky organic cations, manifesting as weak van der Waals interaction, controls the perovskite structure construction as well as charge transport across the individual modules. , Unfortunately, these bulky organic cations joint together via weak van der Waals interaction endow the perovskite building blocks with flexibility of stacking and standing, usually resulting in formation of a multi-quantum well structure with random orientation . Fluorinating the organic spacers has been demonstrated as a valid facile strategy to strengthen the interaction among organic molecules to boost the crystal orientation and phase distribution of 2D Pb-based perovskite during thin-film growth. However, in 2D tin halide perovskites, there is still a lack of understanding about perovskite formation upon tuning of the organic spacer characteristic. Regulating crystal orientation and modulating phase formation by fluorination of organic cations have broad prospects in developing 2D Sn halide perovskites with further improved performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies on 2D perovskite films provide insights into the mechanisms of crystallization and orientation, suggesting that an interlayer interaction among adjacent bulky organic cations, manifesting as weak van der Waals interaction, controls the perovskite structure construction as well as charge transport across the individual modules. , Unfortunately, these bulky organic cations joint together via weak van der Waals interaction endow the perovskite building blocks with flexibility of stacking and standing, usually resulting in formation of a multi-quantum well structure with random orientation . Fluorinating the organic spacers has been demonstrated as a valid facile strategy to strengthen the interaction among organic molecules to boost the crystal orientation and phase distribution of 2D Pb-based perovskite during thin-film growth. However, in 2D tin halide perovskites, there is still a lack of understanding about perovskite formation upon tuning of the organic spacer characteristic. Regulating crystal orientation and modulating phase formation by fluorination of organic cations have broad prospects in developing 2D Sn halide perovskites with further improved performance.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Earlier this year, the first studies on exciton transport in these materials were reported using transient microscopy, directly visualizing the spatial displacement of the excitons as a function of time. [20][21][22][23] Deng et al determined the diffusion constants of a set of 2D perovskites using transient absorption microscopy (TAM), showing how exciton transport improves on increasing inorganic layer thickness n. [20] In parallel, our own group reported on exciton transport in 2D perovskites with varying organic spacers and thicknesses using transient photoluminescence microscopy (TPLM), showing that exciton-phonon coupling is a key parameter in determining the intrinsic exciton transport Transient microscopy is of vital importance in understanding the dynamics of optical excited states in optoelectronic materials, as it allows for a direct visualization of the movement of energy carriers in space and time. Important information on trap-state dynamics can be obtained using this technique, typically observed as a slow-down of energy transport as carriers are trapped at defect sites.…”
mentioning
confidence: 99%
“…[ 2 ] Monolithic tandem cells with the function of adequate utilization of the solar spectrum by combining a narrow‐bandgap absorber with a wide‐bandgap absorber is a feasible way to break through the efficiency limit of single‐junction solar cells. [ 3–8 ] Recently, organic‐inorganic lead halide perovskite solar cells (PSCs) have been proved to be an ideal top cell candidate for preparing monolithic tandem devices using c‐Si bottom solar cells due to their advantages of sharp light absorption edge, [ 9 ] long exciton diffusion length, [ 10 ] tunable bandgap [ 11–13 ] and high efficiency (certification efficiency has reached 25.5% [ 14 ] ). Several groups have reported perovskite/silicon tandem solar cells (PK/c‐Si TSCs) with PCE exceeding 25%, [ 15–30 ] and especially Oxford PV announced an ultra‐high record of 29.5%.…”
Section: Introductionmentioning
confidence: 99%